2024
DOI: 10.3390/molecules29020405
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Characterization: Chemical Oxygen Demand or Total Organic Carbon Content Measurement?

László Wojnárovits,
Renáta Homlok,
Krisztina Kovács
et al.

Abstract: The long time (2 h) required for measurement, expensive chemicals (Ag2SO4), and toxic reagents (K2Cr2O7, HgSO4) limit the application of the standard method for measuring the oxygen equivalent of organic content in wastewater (chemical oxygen demand, COD). In recent years, the COD has increasingly been replaced by the total organic carbon (TOC) parameter. Since the limit values of the pollution levels are usually given in terms of the COD, efforts are being made to find the correlation between these parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
1
1
Order By: Relevance
“…The decrease in TOC is attributed to the transformation of organic carbon into CO 2 [84]. However, in this study, an increase in TOC is identified, which could indicate that organic carbon is not transformed into CO 2 .…”
Section: Influence Of Total Organic Carbon (Toc)contrasting
confidence: 58%
“…The decrease in TOC is attributed to the transformation of organic carbon into CO 2 [84]. However, in this study, an increase in TOC is identified, which could indicate that organic carbon is not transformed into CO 2 .…”
Section: Influence Of Total Organic Carbon (Toc)contrasting
confidence: 58%
“…Chemical oxygen demand (COD) was measured using a Lovibond RD 125 Thermarator (Wojnárovits et al 2024).…”
Section: Characterizationmentioning
confidence: 99%